2022
DOI: 10.1007/s00705-022-05443-5
|View full text |Cite
|
Sign up to set email alerts
|

Recombination drives the emergence of orf virus diversity: evidence from the first complete genome sequence of an Indian orf virus isolate and comparative genomic analysis

Abstract: Contagious pustular dermatitis is a disease that primarily infects small ruminants and possesses zoonotic potential. It is caused by orf virus (ORFV), a member of the genus Parapoxvirus . In this study, we evaluated an ORFV outbreak in goats in Madhya Pradesh, a state in central India, during 2017. The transboundary potential of this virus was evaluated by constructing phylogenetic trees. The complete genome sequence of an ORFV isolate named Ind/MP/17 was found to be 139,807 bp in length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…The strains from outbreak previously reported in Haryana by Kumar et al ( 2014 ) showed 99.98–99.99% nt identity with current strains from the region, implying that the same or closely related strains are involved or circulating in the region. The overall maximum nt identity (99.99%) of current study strains was observed with strain from Rajasthan by Maan et al ( 2014 ) and minimum identity (99.22%) with strains from Madhya Pradesh by Sahu et al ( 2022 ), signifying a close genetic relationship and high conservation of B2L gene (Fig. 4 ) as also previously reported (Maan et al 2014 ).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The strains from outbreak previously reported in Haryana by Kumar et al ( 2014 ) showed 99.98–99.99% nt identity with current strains from the region, implying that the same or closely related strains are involved or circulating in the region. The overall maximum nt identity (99.99%) of current study strains was observed with strain from Rajasthan by Maan et al ( 2014 ) and minimum identity (99.22%) with strains from Madhya Pradesh by Sahu et al ( 2022 ), signifying a close genetic relationship and high conservation of B2L gene (Fig. 4 ) as also previously reported (Maan et al 2014 ).…”
Section: Discussionsupporting
confidence: 86%
“…The B2L gene-based phylogenetic analysis of ORFV in China reported three different genotypes owing to clustering of the virus to different clusters, where Indian strains only clustered with Chinese strains in a single genotype (Zhang et al 2014 ). The previous Indian studies however also reported such clustering and close relation with Chinese strains of ORFV (Maan et al 2014 ; Kumar et al 2014 ; Sahu et al 2022 ) but the clustering of ORFV strains from Nigeria within the same clad with current study isolates provides useful and updated information for further understanding of the biology, epidemiology, and researches towards diagnosis and vaccine development.
Fig.
…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Polymerase chain reaction (PCR) technology targeting specific DNA fragments of ORFV has been widely used for ORFV diagnosis. F1L (ORFV059) gene and B2L (ORFV011) gene are the most commonly used targets for ORFV diagnosis while other conserved genes of ORFV can also be selected as candidates (Sahu et al 2022;Wang et al 2019a, b, c). First, the virus genome is extracted from clinical samples using a viral genome extraction kit.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%